Wychowanie integralne jako emancypacyjna przestrzeń edukacji religijnej - Danuta Wajsprych (Nicolaus Copernicus University in Toruń, 2008)
The integral education as liberation space of religious education   It is the content of article the conception of the integral education which postulates towards full moon of human nature general process of the pupil's development. The man, is the basic centre of conception the complexity of body and the soul, elements - animal and spiritually - divine, and so the full man. Conception this goes out pose man's empirical description, therefore it does not restrain to proposing the pragmatic only model of education. Important it is, to appeal to the man's nature, his vital structure, spiritual culture and her elements, sense of life. Such formulation of object of education shows on occurrence in man's life developmental continuum, which hugs man's whole life and it with this point of sight gathers integral character.